Determination of Tolerance Threshold Level of Golden Snail (Pomacea canaliculata) in Irrigated Rice - Fatmawati Kalau; Franciscus Xaverius Wagiman; Witjaksono Witjaksono (Universitas Gadjah Mada, 2018)
Determination of tolerance threshold of golden snail (Pomacea canaliculata) infestation in irrigated rice had been studied at Sumbersari Village, Moyudan District, Sleman Regency, Yogyakarta Special Teritory, in the growing season of June to October 2016. The water depth during the experiment was maintained at 1 cm. The snails of 2−3 cm in length were infested on rice plots at various ages. The snails were infested on rice plots with density rates of (1) 0, 1, 2, 3, 5, 15, 30, (2) 0, 2, 3, 5, 10, 15, 30, and (3) 0, 3, 5, 10, 15, 20, 30 individuals/m2 at (1) 0 day after planting (DAP), (2) 7 and 14 DAP, and (3) 28 DAP, respectively. These treatments were replicated three times and arranged in the randomized complete block design (RCBD). In this study the tolerance threshold is defined as the highest snail density which causes no significant effect on rice damage and yield loss as compared to control or to the lowest snail density. Therefore, determination of the tolerance threshold was based on the significant difference of damage severity, panicle number per hill, and harvesting dry-weight of rice grain. Results showed that significant rice damage occurred on age of 0, 7, and 14 DAP olds, while on age of 21 and 28 DAP the rice showed no damage. More severe damage occurred to the younger rice. The tolerance threshold values of the snail on rice plots with 1 cm water depth at 0 DAP old was approximately 2 individuals/m2 while at age of 7 and 14 DAP were approximately 3 individuals/m2, respectively. IntisariPenentuan ambang toleransi serangan keong emas (Pomacea canaliculata) pada padi sawah telah dikaji di Desa Sumbersari, Kecamatan Moyudan, Kabupaten Sleman, Daerah Istimewa Yogyakarta dalam musim tanam Juni–Oktober 2016. Kedalaman air selama percobaan berlangsung dikondisikan sedalam 1 cm. Keong berukuran 2−3 cm diinfestasikan pada berbagai umur padi. Keong dengan kepadatan (1) 0, 1, 2, 3, 5, 15, 30; (2) 0, 2, 3, 5, 10, 15, 30; dan (3) 0, 3, 5, 10, 15, 20, 30 ekor/m2 diinfestasikan berturut-turut pada plot padi (1) saat tanam (0 hari setelah tanaman (HST)), (2) umur 7 dan 14 HST, dan (3) serta umur 21, dan 28 HST. Perlakuan diulang tiga kali dan diatur dalam rancangan randomized complete block design (RCBD). Dalam penelitian ini ambang toleransi didefinisikan sebagai kepadatan keong tertinggi yang menyebabkan kerusakan tanaman padi dan kehilangan hasil tidak berbeda signifikan dengan kontrol atau dengan kepadatan populasi terendah. Oleh karena itu nilai ambang toleranasi ditentukan berdasarkan signifikansi perbedaan kerusakan tanaman, jumlah bulir per rumpun, dan berat kering panen gabah. Hasil kajian menunjukkan bahwa kerusakan signifikan terjadi pada padi umur 0, 7, dan 14 hari setelah tanam (HST), sedangkan pada umur 21 dan 28 HST padi tidak menunjukkan kerusakan. Kerusakan semakin parah pada padi semakin muda. Pada kondisi kedalaman air 1 cm, nilai ambang toleransi keong mas pada padi umur 0 HST sekitar 2 ekor/m2 sedangkan pada umur 7 dan 14 HST sekitar 3 ekor/m2.